Pengaruh aras energi dan aras protein pakan terhadap karkas dan lemak abdominal pada beberapa tingkat umur ayam broiler=The Effect of Energy and Protein Levels in the Diets and of Broiler on Carcass and Abdominal Fat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
The study was conducted to determine the effect of energy level (2700, 3000 and 3300 kcal Me/kg), protein level (18 and 22%) diets and age (1-6, 1-7 and 1-8 weeks) of broiler on dressing percentage and abdominal fat (%). Two hundreed and sixteen (216) broilers aged one week, consisting of 108 males and 108 females were used in this study. Each sex was divided into 18 groups (consisted of 6 heads) and every 3 groups were used as replications for each dietary treatment. The result indicated that increasing energy level of those diets improved feed conversion, increases dressing percentage and percentage of abdominal fat (P